Recent Tectonics in the Nepal Himalayas: A Synthesis - Kizaki, K. (Journal of Nepal Geological Society, 1995)
Geodetic surveys were earned out across the Main Central Thrust (MCT) at Dana (Kali Gandaki valley), and the Main Boundary Thrust (MBT) near Kerabari (SW of Pokhara) to obtain quantitative data on the tectonic movements along these boundary thrusts. The results have revealed that the MCT is no longer active, although the surveyed area near the MCT showed a 6 mm tilting to the south in four years. At the same time the surveyed points moved 3-4 cm to the west, indicating that the maximum compressive strain around the MCT in the area surveyed is acting along the NE-SW direction instead of the commonly assumed N-S direction. The measurements across the MBT, on the other hand, showed that the MBT is still quite active with an upliftment of 3 mm in four years. A northward tilt of the area just to the south of the MBT was also recorded. The study of river terraces in the Pokhara area indicated that the overlap of the older Ghachok Terrace by the younger Pokhara Terrace was due to tectonic movements and that the whole area between Pokhara and the upper reaches of the Seti River (north of Pokhara) has tilted to the south since the deposition of the Ghachok Formation or before. The study of river terraces along the Kali Gandaki valley showed that different parts of its N-S section were uplifted at different rates and the most upheaved sections of the terraces were found around Dana (near the MCT) and in the Mahabharat and Siwalik zones since the late Quaternary. The significance of the active faults in the understanding of Recent tectonics in the Nepal Himalayas is also discussed.